Synthesis of tungsten carbide nanopowder by a one-step carbothermal reduction-carbonization method - Kuokuo Bao; Yunzhu Ma; Bolin Zhang; Wensheng Liu (Journal of Materials Research and Technology)
Tungsten carbide (WC) nanopowder is crucial for preparing high-performance WC-Co cemented carbides, but the synthesis of WC nanopowder still remains huge challenges. In this study, we report a novel method for synthesizing high-purity WC nanopowder by carbothermal reduction-carbonization. The effects of the reaction atmosphere, temperature, and time on the morphology and size of WC powder were studied. It was found that vacuum atmosphere was more conducive to prepare WC nanopowder, which could reduce the onset temperature of carbothermal reduction reaction and effectively improve the reaction efficiency. The final products in vacuum were more homogeneous and smaller compared with argon atmosphere. Furthermore, the mechanism of effect of atmosphere on prepared WC nanopowder was analyzed in detail. The particle size of WC showed an increasing trend with the increase of temperature and holding time. Following calcination at 1100 °C for 5 h, the as-prepared WC nanopowder attained an average particle size of 82 nm.